Mother-to-infant and father-to-infant initial emotional involvement - Figueiredo, Bárbara (2007)
While infant attachment has been largely studied, parental attachment is still relatively unknown, especially when referred to fathers. However, it is mainly recognised that parents’ emotional involvement with the newborn contributes to the quality of the interaction and the care they provide. The aim of this study was to study mother-to-infant and father-to-infant initial emotional involvement; namely, differences between mothers and fathers and changes in mother’s emotions toward the neonate within the first days after delivery. The Bonding Scale, an extended Portuguese version of the ‘New Mother-to-Infant Bonding Scale’, was administered during the first two days after childbirth to a sample of 315 mothers and 141 fathers (n = 456), at the Júlio Dinis Maternity Hospital (Portugal). Most mothers and fathers show positive emotions and only a few of them showed negative emotions toward the infant. Maternal and paternal emotional involvement toward the newborn tend to be similar; nevertheless, fathers show less fear and better emotional involvement with the neonate, while mothers are sadder and show more emotions not related to bonding. During the first days following delivery, emotions not related to bonding, such as fear, seem to decrease in mothers.